PENINGKATAN KEMAMPUAN ANALISIS DATA PIKTOGRAM MELALUI VIDEO PEMBELAJARAN ANIMASI BERBASIS AI PADA MURID KELAS V - El Safira, Sofia; Delawanti Chrisyarani, Denna; Tumijan; Sukowati, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ data analysis skills in pictogram material through the use of Artificial Intelligence (AI)-based animated learning videos for fifth-grade students at SDN Pisangcandi 2 Malang City. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, acting, observing, and reflecting stages. The research subjects were 26 fifth-grade students of SDN Pisangcandi 2 Malang City. The results showed that in the pre-cycle stage, the learning mastery percentage was 54% with an average score of 72.46. In cycle I, the mastery percentage increased to 73% in the fairly successful category, with an average score of 80.38. Furthermore, in cycle II, the mastery percentage reached 88% in the highly successful category, with an average score of 88.15. Based on these findings, it can be concluded that the use of AI-based animated learning videos was able to improve students’ data analysis skills in Mathematics subjects.